Penerapan Media Pembelajaran Smart Wheel Game dalam Pemahaman Dokumentasi Kehamilan pada Mahasiswi Semester III Kebidanan - rizqi kamalah; Erni Mayor (JIDAN (Jurnal Ilmiah Bidan), 2022)
Background: The performance achievements of the Indonesian Ministry of Health in 2015-2017 show that there has been a decrease in the number of maternal deaths. One of the activities that support this achievement is midwifery services carried out continuously and perfectly, focusing on the aspect of prevention with other health workers to always be ready to serve anyone in need. The continuity activities in question are in the form of midwifery documentation that records and reports the care given as a reference to demand responsibility and responsibility. Midwifery documentation has been done since college and is one of the requirements for academic graduation but there are still students who do not understand very well about the documentation method. One way that can be used, namely by providing material through playing media in the form of smart wheel games. Purpose: to find out the influence of smart wheel game media in improving the understanding of documentation on midwifery students. Method: The design of this study uses pseudo-experimental methods with pretest-posttest treatment design and one group control. This design is carried out 2 times before and after assessment. Respondents in this study were 30 midwiferies third semester students. Data analysis using Mann Whitney. Results: Based on statistical tests, pretest scores in 2 groups showed the average value of students' understanding of documentation methods was higher in the control group, while the posttest value was higher in the treatment group with a p value of 0.018 with a strong enough relationship strength that was negatively correlated. Thus there is an influence in the application of smart wheel game learning media in understanding pregnancy documentation.